The association between lichen sclerosus and antigens of the HLA system. - Marren, P; Yell, J; Charnock, F; Bunce, M; Welsh, K; Wojnarowska, F (1995)
Although frequently linked clinically with autoimmune disease, no immunogenetic basis for lichen sclerosus has ever been established. In this study, we examined in detail the HLA antigens of 84 patients with histologically proven disease, compared with 357 controls. Patients with lichen sclerosus did not have the expected HLA A1, B8, DR3, DQ2 autoimmune profile. Instead, DQ7 was present in 39 of 78 (50%) of patients compared with 89 (25%) controls (P < 0.001). In addition, 61 of 78 patients (78%) had either DQ7, DQ8 or DQ9 antigens, or a combination of these, compared with 142 (40%) controls (P < 0.01). Raised levels of DQ7 correspond to a glutamic acid residue at position 45 of the DQB1 locus. Proline amino acids at position 55 of this DQB1 locus could explain the raised levels of DQ7, 8 and 9, and exert a secondary effect. There is preliminary evidence that the immunogenetic profile of patients with this disease may affect disease expression with regard to site and extent of involvement.